Landau-Kleffner Syndrome: A Critical Review of Middle-Eastern Cases - (:unkn) unknown (UNIVERSITATSVERLAG ULM GMBH, 2008)
Landau-Kleffner Syndrome (LKS), classified as acquired aphasia with epilepsy is clinically similar to neurodegenerative and neurodevelopmental disorders of childhood and presents a diagnostic challenge to child psychiatrists, neurologists and psychologists alike. Therefore, the aim of this paper was to provide a critical review of this condition along with a review of cases from Middle-Eastern countries. PubMed search engine was used for literature search and the results were reviewed along with classic descriptions of the syndrome. As a consequence of this search, several discrepancies were noted between criteria defined in ICD-10 and those reported in literature. It was deemed possible that acquired epileptiform aphasia may denote a heterogeneous group of disorders which may have subtypes with variability in pathogenesis along with its association between aphasia and EEG abnormalities. There might also be ail overlap between LKS, autistic regression, Continuous Spikes and Waves in Slow Sleep (CSWS), rolandic epilepsy with speech dyspraxia/opercular syndrome and cognitive regression with occipital epileptiform discharges. This relationship may be mediated by nerve growth factors and autoantibodies. Serotonin might play a role as well.
Keywords: Landau-Kleffner syndrome; epilepsy; autism; neuro-immunology; EEG; neuro-psychology; AUTISTIC EPILEPTIFORM REGRESSION; SPECTRUM DISORDERS; CHILDREN; EPILEPSY; SCLEROSIS; APHASIA; SLEEP